Examining the effect of the integration of multiple MALL applications on EFL students’ academic vocabulary acquisition: a mixed-methods study - Hisham Bakhit Said Ghafram Al Shihri; Omer Hassan Ali Mahfoodh; Alla Baksh Bin Mohd Ayub Khan (Cogent Education)
This study examined the effects of integrating three Mobile Assisted Language Learning (MALL) applications—Kahoot, Quizlet, and WhatsApp—on EFL learners’ academic vocabulary acquisition. The study also explored EFL learners’ experiences in using these three MALL applications as academic vocabulary learning tools. In this explanatory sequential mixed-methods study, 60 second- and third-year university students enrolled in an English for Academic Purposes (EAP) course were equally assigned to experimental and control groups. The intervention period lasted 10 weeks. Data were collected from pre-test and post-test academic vocabulary tests and semi-structured interviews. Students in the experimental group were taught using the three MALL applications as academic vocabulary learning tools, while students in the control group were taught using traditional methods. Quantitative data were analysed using descriptive and inferential statistics, while the qualitative data were analysed thematically. The findings revealed a significant improvement in the experimental group participants’ post-test results compared to their control group peers. Moreover, participants in the interviews expressed largely positive views on the effectiveness of the three MALL applications as learning tools. The findings shed light on the advantages of integrating MALL applications in improving academic vocabulary acquisition and the overall learning experience.